2022
DOI: 10.1097/icl.0000000000000890
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Orthokeratology in Myopia Management

Abstract: Intervention to slow axial elongation and progressing degree of myopia has become an important public health issue. Although orthokeratology (OrthoK) has been prescribed to temporarily reduce or eliminate refractive error, myopic children undergoing OrthoK have shown significant slowing of axial elongation and myopic progression. This review presents data on the efficacy, benefits, and risks of the use of OrthoK to slow axial elongation in myopic children. It also discusses how OrthoK fits into an overall stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The NEI-RQL-42, NEI-VFQ-25, and PREP2 are the most studied tools (accounting for 40% of the studies). NEI-RQL-42 61 , 62 , 63 , 64 , 65 and NEI-VFQ-25 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 are more inclined to evaluate functionality, making it suitable for obtaining primary symptoms and quality of life after surgery and treatment. The PREP2 specifically measures ametropia and includes a unique field to measure psychology, specifically peer perception.…”
Section: Discussionmentioning
confidence: 99%
“…The NEI-RQL-42, NEI-VFQ-25, and PREP2 are the most studied tools (accounting for 40% of the studies). NEI-RQL-42 61 , 62 , 63 , 64 , 65 and NEI-VFQ-25 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 are more inclined to evaluate functionality, making it suitable for obtaining primary symptoms and quality of life after surgery and treatment. The PREP2 specifically measures ametropia and includes a unique field to measure psychology, specifically peer perception.…”
Section: Discussionmentioning
confidence: 99%
“…Research also suggests that OK contact lens has favorable efects on children's quality of life, behavior, and psychology [36]. Furthermore, OK contact lens not only corrects myopia but also safely and efectively controls myopia progression [26,[37][38][39], which may make children and parents less concerned about worsening eye condition. Te higher scores of the OK contact lens group in the Proxy PedEyeQ eye care domain are in line with the fndings of Pomeda et al, who found that MiSight contact lenses were associated with higher handling scores than SVS [29].…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were randomly recruited from the Qingyuan People's Hospital of Guangdong Province and Aier Eye Hospital in Qingyuan, China. Following previous studies, patients aged 12–17 years with myopia of −0.50 (D) to −5.00 diopters (D) and refractive errors with astigmatism (rule) of <1.50 D [ 26 ] who had been wearing OK contact lenses (for at least 8 h per night) or SVS for at least 12 months and had no systemic or ocular diseases were included. The children and their parents/legal guardians filled out the PedEyeQ on-site after routine eye examinations.…”
Section: Methodsmentioning
confidence: 99%
“…As a nonsurgical, reversible physical correction of ametropia, orthokeratology has been extensively validated for its safety and effectiveness in controlling the progression of myopia in adolescents. 6,28 At present, there are two designs of orthokeratology in the world: corneal refraction therapy (CRT) and VST.…”
Section: Discussionmentioning
confidence: 99%